Unpacking Identity Construction and Negotiation of a Student Studying Abroad: A Phenomenological Study - Shafina Nur Fitria; Rizky Fatma Amalia; Aniskha Tri Gusniawati; Misdi; Apandi; Nor Syamimi Iliani Che Hassan (Inspiring: English Education Journal, 2025)
This study aims to explore how an Indonesian doctoral student form and negotiate their identities while studying in the United States. Using a phenomenological approach, this study explores participants' experiences in detail through semi-structured interviews. The results show that the process of identity construction was dynamic and influenced by linguistic, academic, social and technological challenges. The participant experienced barriers to understanding informal English, intensive academic pressure and the demands of writing in native speaker standards. However, the participant showed resilience by strengthening their identities through time management strategies, independent learning using digital technologies, and identity reinforcement through everyday activities, especially cooking. These activities not only served as practical skills, but also as a medium to maintain emotional stability and cultural connection. This research confirms the importance of continued investment in cultural skills and learning languages as part of the cultural adaptation process. The results recommend that higher educational institutions provide contextualized support and be more sensitive to international students’ needs as they construct academic and social identities in a global environment.